Issues and controversy of Bt cotton in India 2004-2014: A review - S. Saravanan (Atlantic Review of Economics, 2016)
Bt Cotton, is genetically engineered with Bt (Bacillus thuringiensis), a bio-toxin which comes from soil bacteria. Bt which was isolated from soil in 1911, has been available to farmers as an organic pesticide since 1930.The engineered Bt gene produces a protein that cuts into the guts of specific insects, rendering the cotton resistant to these insects. Biotechnology for control of bollworms is made available in the seed itself. Farmers have to just sow the Bt cotton seeds as they do with conventional seeds. The resulting plants have the in-built ability to produce Bt protein within their body and defend themselves from bollworms. No extra efforts or equipment are needed to utilize this technology. But after the introduction of Bt cotton it brought into focus a variety of issues like economic, environmental and health and it has a controversy against to adopt it. From the review it was found that Bt cotton increased 88 per cent in profitability, increased 31 per cent in yield gains and a significant 39 per cent of reduction of insecticide usage. The range of pesticide reduction varied from 33 per cent to 77 per cent and increase effective yield from 9 per cent to 37 per cent. However, pointed out that economics of Bt cotton was not favourable to farmers because of the seed cost was about four times more expensive than the good local hybrids but price offered to Bt cotton will be higher than that of non-Bt cotton. The adoption of bio-tech crops would reduce the 352 million kg less pesticide used by the Bt growers. As a result of less insecticide uses, the farmer's health was not affected because compared to developed countries, the farmers spray pesticides manually in India.
Keywords: 330; Bt cotton; Health; Pesticide; Profit; Controversy